2020
DOI: 10.3390/ijms21197184
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Irisin in Vascular Function and Atherosclerosis: A Review

Abstract: Exercise is an effective intervention for both the prevention and the treatment of obesity and insulin resistance because skeletal muscle secretes many bioactive proteins that contribute to the beneficial effect of exercise. It has been revealed that irisin plays an important role in metabolic homeostasis and both acute and chronic exercises increase circulating irisin in experimental animal models and in humans. Although previous studies have reported that the irisin-related signaling mechanism may play a ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…A pre-vious meta-analysis including 23 studies showed that compared with non-diabetic controls, circulating irisin concentrations were significantly lower in patients with T2DM [10], suggesting a potential protective role of irisin for glycemic metabolism. This is also consistent with the findings from experimental studies, which confirmed various benefits of irisin in patients with T2DM, such as anti-inflammation, improving insulin resistance, and possibly anti-atherosclerosis [11][12][13][14][15]. Besides, lower serum level of irisin has been observed in T2DM patients with macrovascular complications [16,17], while previous studies evaluating the association between serum irisin and DN showed inconsistent results [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 89%
“…A pre-vious meta-analysis including 23 studies showed that compared with non-diabetic controls, circulating irisin concentrations were significantly lower in patients with T2DM [10], suggesting a potential protective role of irisin for glycemic metabolism. This is also consistent with the findings from experimental studies, which confirmed various benefits of irisin in patients with T2DM, such as anti-inflammation, improving insulin resistance, and possibly anti-atherosclerosis [11][12][13][14][15]. Besides, lower serum level of irisin has been observed in T2DM patients with macrovascular complications [16,17], while previous studies evaluating the association between serum irisin and DN showed inconsistent results [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 89%
“…PGC-1α and FNDC5 expression and increment in circulating level of irisin are known to enhance energy consumption and stimulate the browning of white adipose tissue (WAT), thereby ameliorating insulin resistance [ 3 ]. In addition, recent studies have reported that irisin had a protective effect on the dysfunction of pancreatic β cell [ 4 , 5 ] and vascular dysfunction [ 6 ]. In this regard, irisin is attracting attention as a signaling mechanism that can be used to treat metabolic diseases such as obesity, insulin resistance, and metabolic syndrome because it increases the expression of uncoupling protein 1 (UCP1) present in the inner membrane of mitochondria, thereby inducing the browning of WAT.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, FNDC5/Irisin is considered as a direct transcriptional target of FXR, and may be a novel therapeutic strategy for dyslipidemia and atherosclerosis. Several studies have mentioned that irisin inhibits neointima formation, endothelial injury and inflammation in Apoe-/-mice model (12), Irisin reduced oxidized low density lipoprotein (oxLDL)-mediated endothelial cell apoptosis, inflammatory cytokines and intracellular ROS levels, and up-regulated p-AKT/ mechanistic target of rapamycin (mTOR)/NF-E2related factor 2 (Nrf2). In addition, mTOR/Nrf2 shRNA and LY294002 both ameliorate the protective effect of irisin, suggesting that irisin alleviates oxLDL-induced vascular injury through activation of Akt/mTOR/Nrf2 pathway (13).…”
Section: Introductionmentioning
confidence: 99%